A linear cavity brillouin/bismuth-based erbium-doped fiber laser with enhanced characteristics - Shahabuddin, Nurul Shahrizan; Harun, Sulaiman Wadi; Shirazi, Mohammadreza Rezazadeh; Ahmad, Harith (IOP Publishing, 2008)
A new linear cavity BEFL configuration for increased Stokes-line generation is proposed and demonstrated utilizing a 2 × 2 coupler at the end of the linear cavity. The proposed linear cavity is able to generate up to 33 Stokes lines in the 1590-nm region at a channel spacing of 0.089 nm. The Stokes lines are generated at a BP power of 4 dBm and a 1480-nm pump power of 100 mW. The number of Stokes generated by the proposed BELF is higher compared to conventional BEFL configurations in which the 2 × 2 coupler is placed in the middle of the linear cavity. The number of Stokes lines generated is observed to depend on the 1480-nm pump power as well as the operating wavelength region, which must be as close as possible to the lasing bandwidth of the free-running BEFL. The proposed multiwavelength BEFL is able to operate stably at room temperatures and is also compact due to the use of a 215-cm bismuth-based EDF as the linear gain medium.